A NEW SPECIES OF MANGIFERA (ANACARDIACEAE) - Ding Hou (Reinwardtia, 1972)
There are only two species of Mangifera, M. duperreana Pierre from Indochina and M. lagenifera Griff, from Malay Peninsula and Sumatra, which were described to have flowers with 10 (—12) stamens, of which 5 (or 6) are fertile. In the latest monograph of the genus by Mukherji (in Lloydia 12,1949: 73 — 136), they were placed in two different sections (without naming the sections). According to him, the floral morphology of these two species shows that they "possess the most primitive feature in the genus (pentacyclic flowers)" (cf. J. Linn. Soc. Bot. 55, 1953: 75). In the course of revising this genus for the Flora Malesiana, a new species having flowers with also ten stamens was discovered, which has been named and described here as Mangifera decandra (= ten-stamened; in Gk: deca-, ten; andro-, male) ; its epithet alludes to the significant number of stamens.